1991
DOI: 10.1084/jem.174.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor induces development of connective tissue-type mast cells in vitro from murine bone marrow cells.

Abstract: SummaryThe effect of nerve growth factor (NGF) on proliferation/differentiation of mast cells was investigated in vitro. Although NGF alone neither supported colony formation of bone marrow-derived cultured mast cells (BMCMC) nor induced development of mast cell colonies from nonadherent bone marrow cells (NBMC), addition of NGF to the suboptimal dose of interleukin 3 (IL3) significantly increased the numbers of mast cell colonies produced by BMCMC or NBMC in methylcellulose. When stimulated by IL3 alone, cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(105 citation statements)
references
References 34 publications
6
99
0
Order By: Relevance
“…In addition to neurotrophic activity, increasing evidences give rise to possible multifunctional properties of NGF on immunocompetent cells including lymphocytes, monocytes/macrophages, and mast cells through functional NGF receptors (4 -11). In prior studies, we have demonstrated that NGF promotes not only granulocyte differentiation from human PBMC and murine bone marrow cells (12,13), but also differentiation of connective tissue-type mast cells from murine bone marrow cells and bone marrow-derived culture mast cells (14). NGF is capable of supporting survival of neutrophils (15), eosinophils (16), and mast cells (9) by preventing apoptosis, and enhancing functional properties of neutrophils, eosinophils, macrophages, and mast cells: phagocytosis, superoxide production, matrix metalloproteinase-9 production, and chemotaxis (11, 12, 16 -20).…”
Section: N Erve Growth Factor (Ngf)mentioning
confidence: 99%
“…In addition to neurotrophic activity, increasing evidences give rise to possible multifunctional properties of NGF on immunocompetent cells including lymphocytes, monocytes/macrophages, and mast cells through functional NGF receptors (4 -11). In prior studies, we have demonstrated that NGF promotes not only granulocyte differentiation from human PBMC and murine bone marrow cells (12,13), but also differentiation of connective tissue-type mast cells from murine bone marrow cells and bone marrow-derived culture mast cells (14). NGF is capable of supporting survival of neutrophils (15), eosinophils (16), and mast cells (9) by preventing apoptosis, and enhancing functional properties of neutrophils, eosinophils, macrophages, and mast cells: phagocytosis, superoxide production, matrix metalloproteinase-9 production, and chemotaxis (11, 12, 16 -20).…”
Section: N Erve Growth Factor (Ngf)mentioning
confidence: 99%
“…The marked effect of SCF was noted even after preincubation for 1 h and most BMCMC preincubated for 48 h remained in the upper compartment. NGF, which is produced by fibroblasts as SCF, promotes differentiation and chemotaxis of mast cells (9,49). Therefore, we examined its effect on the IgEmediated chemotaxis of BMCMC.…”
Section: Inhibition Of Bmcmc and Hucmc Chemotaxis Toward Igespecific mentioning
confidence: 99%
“…Mature CTMCs contain more histamine and heparin, which is specifically recognized with berberine sulphate, than those in mucosal type mast cells. Both of these types of mature mast cells can be mutually interconverted by simply altering the culture conditions in vitro or the environment in vivo (Matsuda et al 1991). Thus, these two classes of mature mast cells have clearly defined and unique characteristics; the molecular determinants which specify their differentiation, in contrast, are not understood.…”
Section: Introductionmentioning
confidence: 99%